An analysis of IMF conditionality - Buira, A (University of Oxford, 2002)
Conditionality is the most controversial aspect of the IMF's policies. It has been said to be intrusive and coercive and considered to disregard effects on growth, employment and income distribution. In the 1990s, following a sharp increase in the number of conditions required by programs, Fund conditionality became increasingly ineffective. The paper reviews the nature and purpose of conditionality; its origin and evolution over time. It considers whether conditionality is required to safeguard the resources of the Fund. It looks into the reasons for the increase in structural conditionality, relates the increase in conditionality with the marked fall in the rate of compliance with Fund programs and with the relative decline in Fund resources. The paper notes the revision of conditionality recently undertaken at the instance of the Managing Director and considers progress on that front. Finally, certain difficult political questions arising from conditionality are posed and some suggestions presented for increasing country ownership of programs, the key to making conditionality more acceptable and effective.